Biosensors for Organophosphorous Pesticides and Development of a Portable Prototype based on ISFET - Patial, Baneesh (My University, 2017)
The present work focuses on the development of biosensors for the determination of organophosphorous pesticides based on Chlorella sp. Two types of biosensors have been proposed (i) a potentiometric portable biosensor by modifying Ta2O5 ISFET with alkaline phosphatase enzyme present on the surface of Chlorella sp. (ii) an amperometric biosensor based on PS II system of algae. Potentiometric biosensor was tested for pesticides namely acephate, triazophos, chlorpyrifos and malathion. It showed good selectivity and sensitivity towards acephate and triazophos. The detection principle was based on the inhibition of alkaline phosphatase enzyme by pesticides, monitored through the formation of product ascorbic acid. Acephate and triazophos shows linear response in the concentration range of 10-10 M to 10-2 M, whereas with malathion no regular trend was observed. Proposed biosensor was further tested for real time samples and validated with HPLC. Proposed prototype showed good reproducibility and sensitivity, thus, it could be used for on-site detection for pesticide detection. Amperometric detection of pesticides based on their interaction behaviour with PS II system of Chlorella sp. has also been studied. The study was performed in both free and immobilized state. Results showed that the sensor showed linear response with acephate and triazophos with their increasing concentration. However, the trend was different in free and immobilized state. In case of free algal biosensor, acephate increase the current magnitude with respect to control and showed linearity up to 10-8 M. Whereas, triazophos decreased the current linearly in the range of 10-8 M to 10-2 M. The immobilized algal biosensor showed entirely different trend from free state due to cross linking of algae with glassy carbon in glutaraldehyde environment. Due to this reason, the current obtained for acephate and triazophos should independent behaviour at electrode surface. Acephate and triazophos increases the magnitude of current and showed linear response of output current to 10-7 M and 10-9 M, respectively.
Keywords: Portable Potentiometer; Organophosphorous; ISFET; Chlorella sp.; Chronoamperometry